Salt food conservation techniques as a practice of traditional knowledge from the Community of Murutinga, Abaetetuba - Pará - Ana Paula Vilhena Farias; Yomara Pinheiro Pires; Lourivaldo da Silva Santos; Marcos César da Rocha Seruffo; Manoel Leão Lopes Junior (Universidade Federal do Norte do Tocantins, 2022)
Traditional knowledge has for a long time been the only way of teaching that was a source of income for many and provided for their survival. With the advent of modernity, the technique of salting food has lost space for the food refrigeration and freezing system, but this knowledge is of paramount importance to keep alive the culture and identity of communities, such as Murutinga, in the municipality of Abaetetuba, Pará This production had as proposal to know the process used for salting of the food besides analyzing how this knowledge was acquired and its importance for future generations. Among the procedures adopted, we sought reports from former residents describing the methods used to conserve foods such as meat, fish and shrimp through salting, simultaneously carrying out a bibliographic study in order to address and subsidize the analysis of their inherent biochemical processes. The results show that there is still a strong presence of this traditional knowledge in the locality investigated, so that the practice of salting is still being carried out in this area, with emphasis also on the efforts of the elders to spread this practice to the young people of the community.